EXPLORING THE ONTOLOGICAL BASIS OF LAW: JOSEPH RAZ'S VIEWS ON NORMATIVITY WITHIN THE FRAMEWORK OF LEGAL REALISM - Silalahi, Artha Debora ADS; Mustansyir, Rizal; Tjahyadi, Sindung (UI Scholars Hub, 2025)
This study explores the moral ontology of law within the framework of Legal Realism, contextualizing law as both a social institution and an institution of justice. Drawing on Joseph Raz's perspectives on practical reason, normativity, and the foundations of norms, the analysis examines how law, as a practical guide, inherently carries moral dimensions in regulating social interactions and pursuing justice. Legal Realism frames law as a dynamic product of human interaction within a social context, while Raz's philosophical insights illuminate the interplay between practical reasoning, normativity, and legal structures. By focusing on the moral underpinnings of legal norms, this paper seeks to address how law as an institution can uphold social legitimacy while meeting the demands of justice. The analysis offers a conceptual framework to understand the role of moral ontology in modern legal systems, particularly in navigating legal pluralism and societal complexity.